GIS FOR BANKING: THE DEVELOPMENT OF SPATIAL MODEL FOR LAND VALUATION IN SURABAYA - Hening Widi Oetomo (Journal of Economics, Business, and Accountancy Ventura, 2010)
Land value is used for collateral valuation in Indonesia. This system is considered officially stamped on a property tax. In addition, the property tax uses Land Value Zone (LVZ) for land valuation. The purpose of this research is to produce a land valuation method, namely individual valuation based on enviromental situation in certain land location. The research produced three models namely structural model, location model and spatial model. The results showed that structural factor contributed to land value variation at 56.5% and location factor contributed to land value at 36.7%. Furthermore, spatial model represented a combination of structural and location models. Tha spatial model contributed to land value variation is at 73%. The remaining 37% was influenced by non-spatial factors such as legality, economic situation and another factors. The iimplication of this research is that, there is more fair land assessment because it is an individual one. However, the main problem in this case is that it needs different models for different areas. Suggestion for future research is simplifying the variables that are used in order to make them able to be applied in a certain wider area. The variable simplification is important because the data supply in Geographical Information System (GIS) is expensive